Структуризація процесу виконання завдань з надання впевненості, інших ніж аудит чи огляд історичної фінансової інформації - Андрощук, І. І.; Androshchuk, І. (ЦНТУ, 2017)
Досліджено організаційні положення завдань з надання впевненості, інших ніж аудит чи огляд історичної фінансової інформації, в частині обґрунтування послідовності етапів виконання та їх наповнення. Як вихідну базу для структуризації процесу виконання завдань з надання впевненості, інших ніж аудит чи огляд історичної фінансової інформації, запропоновано використовувати підхід до виділення таких етапів: етап прийняття завдання; етап отримання й оцінки доказів; етап завершення завдання. Обґрунтовано, що запропоновані послідовність і наповненість етапів виконання завдання уможливлюють чітку ідентифікацію видів завдань та їх елементів, забезпечують якісне виконання завдань відповідно до Міжнародних стандартів контролю якості, аудиту, огляду, іншого надання впевненості та супутніх послуг. The purpose of this study is to develop organizational provisions for assurance engagements other than audit or review of historical financial information, in particular the substantiation of the main stages of their performing. As an initial basis for structuring the process of performing assurance engagements other than audit or review of historical financial information, it is proposed to use an approach to the selection of the following stages: preparatory-agreeing (stage of the acceptance of engagement); basic (stage of obtaining and evaluating of evidence); ɫompletive-agreeing (stage of completion of the engagement). It is substantiated that such sequence and the proposed fillability of the stages of the engagement performance allows for a clear identification of types of engagements and their elements, ensures their qualitative performance in accordance with the International standards of quality control, audit, review, other assurance and related services. Further research should be carried out in the direction of developing standard forms of a general strategy and plans for carrying out various types of assurance engagements depending on the subject matter, which will be adequately addressed to meet the conditions of a specific engagement that will improve the quality of the auditor's work and the quality of the process of performing assurance engagements.
Structuring the process of performing assurance engagements other than audit or review of historical financial information
Keywords: аудиторська діяльність; завдання з надання впевненості; інше ніж аудит чи огляд історичної фінансової інформації; міжнародні стандарти; етапи виконання завдання; audit activity; assurance engagement other than audit or review of historical financial information; international standards; stages of performing the engagement